Factors Influencing the Purchase Intention of Green Product among STML Student - Abdullah, Nur Syafawati; Saad, Rohaizah (Universiti Utara Malaysia, 2019)
The last decade, environmental pollution has risen and has increased global warming. This study presents an attempt to examine the factors that will affect the purchase of green products and save the environment from pollution. The findings of this study include environmental consciousness, environmental knowledge, environmental attitude and environmental benefit against the intention of purchasing green products. The sample of this study is 100 respondent randomly in UUM undergraduate students of Operation Management, Technology Management and Logistics & Transportation from School of Technology Management and Logistics (STML) have been selected to participate to achieve the objectives of the study. The figure of framework will created in this study to look the relationship between independent variable and dependent variable. The data collection, researcher used Statiscal Package for Social Science (SPSS) software.